Marco Polo i manichejczycy z prowincji Fujian - Malinowski, Gościwit (Gajt Wydawnictwo 1991 s.c., 2018)
This paper is concerned with the passage from The Travels of Marco Polo in which mysterious religious community in the city Fuzhou is described. Maffeo and Marco Polos recognised this community as Christians, however, in our times most scholars are following the idea of Paul Pelliot that Polos actually met with Manichaeans. The Fujian province was a refuge for Chinese Manichaeans since Five Dynasties and Ten Kingdoms period, long before the Mongol conquest of Southern China. After the fall of Yuan dynasty, Manichaean communities in the Fujian province continue their existence despite the persecutions ordered by Ming authorities. The majority of scholars think that Manichaeism ceased to exist as a separate religion in the 17th century when the last Chinese Manichaeans had dispersed among heterodox Buddhist and Taoist communities. Today, the most eminent Manichaean remnants in Fujian province is the Cao’an temple in Jinjiang.
Keywords: Marco Polo